Pengaruh Kualifikasi Pendidikan Terhadap Produktivitas Karyawan Di Perusahaan Tekstil: Sebuah Analisis Regresi Linear Sederhana - Arifin, Indra Rahmat; Kustiwa, Atep (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
Employee productivity is a crucial factor in a company's success. Educational qualifications are believed to enhance skills and work efficiency. However, in some companies, employees with lower education levels exhibit productivity nearly equal to those with higher education. This study aims to analyze the impact of educational qualifications on employee productivity. A quantitative research method was used with simple linear regression. Data was collected through questionnaires from 30 respondents in the studied company. The analysis results indicate that educational qualifications significantly affect productivity. The t-test produced a t-value of 2.919 with a p-value of 0.007 (<0.05), leading to the rejection of H₀. The regression coefficient (B) of 0.443 suggests that each unit increase in educational qualification raises productivity by 0.443 units. The coefficient of determination (R²) of 0.233 indicates that 23.3% of productivity variability is influenced by educational qualifications, while 76.7% is affected by other factors such as work experience and skills. In conclusion, educational qualifications impact employee productivity, but other factors also play a significant role. Companies are advised not only to consider education levels in recruitment but also to enhance training and skill development to optimize employee productivity.